DESAIN PROGRAM APLIKASI MICROSOFT VISUAL BASIC PADA MATERI BARISAN MATEMATIKA SISWA SMP KELAS VIII - Vivi Novi Anjani; Rohana R; Asnurul Isroqmi (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2022)
The purpose of this research is to produce a Microsoft Visual Basic application program on arithmetic sequence material that is valid, practical, and effective. The development model used is the ADDIE model with data collection instruments in the form of questionnaires, tests and documentation. Based on the results of this study, the following results were obtained, the results of the validity analysis stated that the developed media was valid with a score percentage of 83.8%, the results of the practicality analysis stated that the developed media was practical with a percentage of 93.3%, and the results of the effectiveness analysis stated that the developed media was effective. with a percentage of 86.6%.